OPTIMALISASI PERAN BMT DALAM UPAYA PENGHAPUSAN PRAKTIK RENTENIR - Ayogi, Visita Dwi; Kurnia, Tuti (JURNAL SYARIKAH : JURNAL EKONOMI ISLAM, 2015)
The existence of the moneylender more exist until now,this is evidenced by the fact that 70 % of SMEs caught on moneylenders. Such a practice is clearly to be abolished in the community because of the negative impact for the community. Therefore, the existence of Baitul Maal wa tamwil (BMT) as a microfinance institution which is operated by the Islamic principles is considered very important to eliminate the practice of moneylenders in the community. The purpose of this study was to determine the role that has been carried out by BMT in efforts to eliminate the practice of moneylenders and to determine the role played by BMT is optimal or not in efforts to eliminate the practice of moneylenders.Dataanalysistool in this study using quantitative descriptive analysis data collection through interviews.Data processing is done by using lnear programming, with the help of an application program LINDO, to complete the mathematical modeling used to optimize an objective with various constraints. Were then analyzed by analysis of primal, dual, and sensitivity.The conclusion of this study is the role performed by BMT Amal Atina and BMT Berkah Mandiri Sejahtera in efforts to eliminate the practice of the moneylender is not optimal, because the resources used to minimize the practice of excessive or moneylenders in the community still has not been used optimally.Keywords :Role of BMT , the Moneylender .